Strategi Da’wah Penyuluh Agama Dalam Pembinaan Masyarakat: (Studi Analisis Strategi Penyuluh Agama di Kemenag Kab. Bireuen) - Muslem Hamdani (Fakultas Syariah dan Ekonomi Islam, 2021)
This study aims to explore the Among the institutions that are responsible in the religious ceremony in Indonesia is the Ministry of Religious Affairs through Religious Counselors. Extensionists of Islam today face a rapidly changing society condition that leads to functional communities, technological societies, scientific societies and open societies. The success of an extension of Islamic Religion in carrying out its duties in the community is influenced by several components of which the da'wah strategy components are chosen and formulated. Thus, the formula of the problem is: First How Strategy Extension Agent Kemenag Bireuen District in running community development, What are the opportunities and challenges of religious instructors in Kemenag Kabupaten Bireuen in actualizing his da'wah strategy. Data collection in answering the problem, the authors use qualitative descriptive research method that is research on how strategic da'wah in coaching conducted by the Bireuen Islamic Religious Counselor for the community. The results showed that da'wah strategy in coaching is almost right although there are still many obstacles faced while doing coaching. Until these findings bireuen people have begun to understand the importance of studying Islam properly. The pattern of guidance to the most important community through majelis taklim, art development, education and religious courses for couples pre marriage and so forth. In coaching other than done by counselors also present the scholars as speakers.